Effects of Yoga on Blood Pressure and MDA in Mild Hypertensive Patients. (Academia Journal of Medicine, 2018)
Background: Cardiovascular diseases (CVD) have emerges as the leading cause of mortality throughout the world. Essential hypertension is  one of the important risk factor for CVD in modern society despite advanced and effective management. Malondialdehyde (MDA) is a well  known marker of oxidative stress, which is produced by oxidation of poly unsaturated fatty acid. Nadishodhan pranayam leads to decrease  stress as well as blood pressure. Subjects and Methods: It was an interventional type of study. Ninety seven mild hypertensive patients (53  males and 44 females) of group I completed the yoga program. While, fifty normotensive subjects were include as control in group II. Blood  pressure and MDA was measured of every participants before and after three months of yoga program. Results: Total ninety seven mild  hypertensive patients of age 33.6± 8.66 years of group I completed three months yoga program. However, fifty subjects (34.7± 7.73 years)of  group II had not done any yogic exercise during three months. Results of the present study showed that there was a significant difference in  SBP (p
Keywords: Yoga; hypertension; MDA; CVD